Heterogeneity of Immunological, Coagulation and Complement Clustering to Viral Challenge and Clinical Relevance - Dandan Zhu; Pawel Zmuda-Trzebiatowski; Daniel Diedrich; Krzysztof Laudanski (International Journal of Molecular Sciences, 2026)
Differences in immune responses affect viral illness outcomes, but the combined contributions of inflammation, coagulation, and complement pathway heterogeneity to disease stratification remain unclear. We analyzed infectious, immunological, coagulation, and complement responses at admission (t0) and assessed their associations with cerebrovascular and coagulation comorbidities. Ninety-six PCR-confirmed SARS-CoV-2 patients were sampled at